Incidence of Ostertagia ostertagi and Ostertagia lyrata in calves during the dry period in the state of Rio de Janeiro, Brazil - Bianchin, Ivo (Pesquisa Agropecuaria Brasileira, 2014)
The incidence of Ostertagia ostertagi and Ostertagia lyrata in cattle was studied from May to October 1977 in 48 male calves from the State of Rio de Janeiro, Brazil. The work based on faecal examinations and monthly necropsies. The highest incidence of Ostertagia spp. occurred in September and the highest number found in one calf was of 262 specimens. It was found that 62.5% of the necropsied calves were infected by Ostertagia species, 97.4% being O. ostertagi and 2.6% O. lyrata. This is the second time O. ostertagi and the first time that O. lyrata have been cited in the State of Rio de Janeiro. Due to their low incidence, Ostertagia spp. are not considered to be of epizootiological importance for cattle production in the State of Rio de Janeiro, Brazil.